Relationships differentiation: Cross-ethnic comparisons in the Malaysian workplace - Abu Bakar, Hassan; Halim, Haslina; Mustaffa, Che Su; Mohamad, Bahtiar (Routledge, 2016)
This research examines how Malaysian managers and employees interpret and embody leader–member relationships differentiation.To analyze this question, we conducted a thematic analysis of top management, middle management and supporting dialogue group discussions.Results showed that leader–member relationships differentiation is a symbol that is essential for the creation and sustenance of leader’s conceptual skills, communication openness, respect, trust, and age differentiation.These findings validate our proposition of leader–member relationships differentiation in Malaysian workplace and empirical support for the central roles of communication exchange processes in workgroups.